Media Pembelajaran Abad 21: Kebutuhan Multimedia Interaktif Bagi Guru dan Siswa Sekolah Dasar - Ahmad Habib; I Made Astra; Erry Utomo (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2020)
The purpose of this research is to analyze Science learning and the use of interactive multimedia in elementary school. The methods used are qualitative and quantitative. The population of teachers and elementary school students. Samples were taken randomly, set at 6 SDN in Pati District. The instruments used in this study are questionnaires and interview sheets. The results showed, interactive multimedia programs are needed, especially to support the abstract science learning, especially the human circulatory organ material. The desired Format is a multimedia integrated with a project-based learning model with an extra game of problems. To facilitate teachers and elementary school students need to develop interactive multimedia that includes project-based learning, project development, and project-report output. In addition, it is necessary to develop game problems that can show results as well as evaluation of the game problem. Game problems are tailored to the level of cognitive development, affective, and psychomotor of elementary school students.